Fostering The Future: Examining The Meaning Of Life And Optimism In Generation Z - Hamdaniati, Aliyatil (Universitas Islam Negeri Raden Mas Said Surakarta, 2025)
The study of meaning, in philosophy and psychology, is important to reveal the influences on individual well-being, including optimism. This systematic literature review examined various factors, such as social media, family environment, education, and personal experiences, influencing Generation Z's perception of the meaning of life and their optimism. The researcher employed the PRISMA model to select articles included in the study. Age, gender, and spirituality are influential factors in the search for meaning in life. Age influences a person's search for life's meaning and their optimism. Gender also plays an important role; women tend to discover meaning in life through family roles and social relationships, while men tend to find meaning through achievement and independence. Spirituality, such as religious practices and spiritual beliefs, offers individuals a framework to discover the meaning of life and remain optimistic, especially through the social support of the spiritual community.